Experimental study on low temperature heating performance of different vapor injection heat pump systems equipped with a flash tank and economizers for electric vehicle. (5th June 2023) - Li, Kang; Ma, Jingru; Zhang, Bin; Su, Lin; Liu, Ni; Zhang, Hua; Dou, Binlin; He, Qize; Zhou, Xuejin; Tu, Ran
Highlights: Vapor injection heat pump systems using a flash tank and an economizer are designed. The economizers are designed using both upstream and downstream injection path. The maximum heating capacities in the injection systems rise by 19.7 %, 22.6 %, and 92.3 %. The optimal 0.16–0.37 MPa injection pressure range is determined by the maximum coefficient of performance. The downstream injection system and flash tank vapor injection system show better experimental heating performances. Abstract: One of the most promising solutions is applying vapor injection technology to improve the heating performance of air conditioning heat pump systems in electric vehicles operating at extremely low temperatures. This study examined the effects of employing flash tank vapor injection (FVI) and economizer vapor injection (EVI) with both upstream injection (UI) path and downstream injection (DI) path configurations on a vapor injection heat pump system with a small ratio vapor injection scroll compressor. Experiments were conducted to record the system performance at low temperatures, and typical heat transfer characteristics were obtained with different expansion valve opening degrees and compressor speeds. The influence of the injection pressure on the system performance was also investigated, and the optimal injection pressure was determined. The results for the upstream injection, downstream injection and flash tank vapor injection systems indicated maximum increases in the system's heating capacity of 19.7 %, 22.6 %, and 92.3 %, and in its coefficient of performance (COP) of 24.2 %, 16.9 %, and 118 %, respectively; the corresponding discharge temperatures decreased by 12.4℃, 18.99 ℃, and 16.95 ℃, respectively. In addition, the optimal injection pressure was determined according to the maximum value of COP, and the optimal injection pressure range for the system is 0.16–0.37 MPa. Hence, a vapor injection system using an economizer with a downstream path could achieve better heating performance at relatively low temperatures. In contrast, a flash tank would offer some heating capacity advantages at temperatures below −15℃.